Pengaruh Profitabilitas, Leverage, dan Ukuran Perusahaan Terhadap Kebijakan Dividen Pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia - Isma Wati; Tuti Meutia; Nurliza Lubis (Journal Research of Economic and Bussiness, 2026)
This study aims to analyze the effect of profitability, leverage, and company size on dividend policy in energy sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018–2024 period. This study uses a quantitative approach. In this study, profitability is measured by the Return on Assets (ROA) ratio, leverage is calculated using the Debt to Equity Ratio (DER), while company size (Size) is determined based on total assets. Dividend policy as the dependent variable is measured through the Dividend Payout Ratio (DPR). The population in this study amounted to 91 energy sector companies listed on the IDX during the study period. The sampling technique applied was purposive sampling, namely a method of selecting samples based on certain criteria that have been determined by the researcher. By using this method, 70 samples were obtained from 10 companies in the energy sector during the observation period. Data analysis in this study includes classical assumption testing and multiple linear regression analysis using the SPSS program. The results of the tests that have been conducted indicate that profitability (ROA), leverage (DER), and company size (Size) either partially or simultaneously have no significant effect on dividend policy in energy sector companies on the IDX. These findings suggest that dividend policy is more influenced by factors outside the research model. Keywords: Dividend Policy, Profitability, Leverage, Firm Size